FACIES AND STRATIGRAPHIC STUDY OF THE BRANI FORMATION, HARAU VALLEY AND SURROUNDING AREA, WEST SUMATRA - Ilsani, Rifki
The Ombilin Basin is a Tertiary sedimentary basin located in the Bukit Barisan Zone, West Sumatra Province. The rocks of the Ombilin Basin are well exposed, especially the synrift deposits of the Brani Formation and Sangkarewang Formation, which can be used as an analogy for the reservoir geometry of synrift deposits in the subsurface. This study focuses on the lithofacies, facies association, and facies architecture of the Brani Formation. The analysis of facies, facies associations, and architectural facies was initiated by measuring stratigraphic cross-sections on a 5.67 kilometer long track, resulting in a total stratigraphic column thickness of 518m. In addition, petrographic analysis was conducted on 24 thin section samples of sedimentary rocks and maseral analysis on 1 sample of mudstone. Based on the results of stratigraphic cross-section measurements, facies analysis, and constituent components, the research track is composed of 20 lithofacies and 8 facies associations that compose 5 architectural facies namely proximal fan, mid fan, distal fan, deep gravel braided, and anastomosed. Petrographic analysis shows that the main mineral components of rocks in the Brani Formation are quartz and feldspar with an average rock porosity of 4%. The debris flow lobe association in the Palano Area has a constituent mineral component in the form of biotite, but in the Harau Area there is no such mineral. Therefore, it is interpreted that the Harau and Palano Areas have different bedrocks. In addition, the presence of volcanic glass indicates the influence of volcanic activity so that it represents the same age between the Harau, Sarilamak, and Palano Regions. Maceral analysis shows that the depositional environment of the mudstone lithology was in a wet area with intermittent moderate - high flooding conditions indicating the influence of water from the lake. The almost equal ratio of vitrinite and mineral matter and the low percentage of liptinite indicate that the mudstone lithology was formed exsitu.